Gasifier, Solid Oxide Fuel Cell Integrated Systems for Energy Production From Wet Biomass - Recalde, Mayra; Woudstra, Theo; Aravind, P. V. (Frontiers in Energy Research, 2019)
Nowadays, there is worldwide interest in diversifying the energy supply. In this regard, biomass is the best possible renewable organic substitute for fossil fuels. In particular, the energy content of very wet biomass, recovered with appropriate technology, could be potentially used for power generation. In addition to power generation, this technology would represent a sanitary option to improve the quality of public health and the environment. Supercritical water gasification (SCWG) is a technology applied for the conversion of wet biomass into gas. It uses the specific physical properties of water at supercritical conditions to decompose the organic matter. However, near 100% conversion, close to thermodynamic equilibrium, of real biomass into gas is not yet demonstrated. The conversion is higher at dry biomass concentrations below 10 wt.%, but at these conditions, the system is not energetically sustainable. The conversion depends on the SCWG operating conditions and the properties of the catalyst. Because of the present-day technical limitations, the conversion efficiency in SCWG is low when fed with real biomass. The net electrical efficiency of a combined system SCWG ̶ Solid Oxide Fuel Cell (SOFC), fed with faecal sludge at 15 wt.% dry biomass, reaches between 50 to 70% (thermodynamically calculated values) while utilising an SCWG designed with present day engineering gives 29-40%. The SOFC fuel utilisation influences the system efficiency significantly, as the process heat available for the heat integration dependents on fuel utilisation. The extreme operating conditions of an SCWG - based system cause technical limitations towards reaching complete conversion during gasification. An efficient and stable catalyst is not yet available catalysts at competitive costs for low-temperature SCWG of real biomass. Intensive research in different gasification – SOFC system configurations that include the integration of complementary processes, such as the electrochemical oxidation of higher hydrocarbons or the electrochemical reduction of CO2 and H2O, will increase the potential of the gasification – SOFC system for commercialisation in medium-scale in the future, and become a technology that provide economic, environmental and health benefits.